Determinan Kualitas Hasil Audit Inspektorat Lombok Timur - Arini, I Gusti Ayu Laras Dwi Arini; Suhaedi, Wirawan (Fakultas Ekonomi dan Bisnis Unram, 2024)
The aim of this research is to determine the influence of objectivity, integrity, professional skepticism and independence on the quality of audit results. This research is a type of associative research with a quantitative approach. The data used is primary data obtained through distributing questionnaires. The sampling technique used was a saturated sample by taking the entire population to be used as a sample, namely 35 East Lombok Inspectorate auditors. The data analysis toolused is Partical Least Square (PLS) version 4.0. The results of this research prove that objectivity, integrity, professional skepticism and independence have a significant positive effect on the quality of the audit results of the East Lombok Inspectorate. The theoretical implication of this research is to strengthen attribution theory in explaining the role of internal motivation for auditor behavior (Objectivity, Integrity, Professional Skepticism, and Independence) which is significant in thequality of audit results.